The Effect of Internal Control, Utilization of Technology, Compliance with Legislation Regulations on the Performance Accountability of Government Agents (Case Study of Dairi Regency BPKAD) - Sahala Purba; Arison Nainggolan; Edi Ray Lumban Gaol (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2022)
This study aims to determine whether the Effect of Internal Control, Utilization of Technology, Compliance with Laws and Regulations, either partially or simultaneously, has an effect on the Performance Accountability of Government Agencies (Case Study of BPKAD Dairi Regency). The population in this study were 42 respondents. Samples using purposive sampling. Respondents are all employees of the Regional Asset Finance Agency of Dairi Regency. Based on the data analysis process, the classical assumption test was carried out first and then the hypothesis testing was carried out. The statistical method used is multiple regression analysis. The results of this study indicate that simultaneously Internal Control, Utilization of Technology, Compliance with Laws and Regulations together have a significant positive effect on the Performance Accountability of Government Agencies. Partially, Internal Control has a positive and insignificant effect on the Performance Accountability of Government Agencies, the Utilization of Technology has an insignificant positive effect on the Performance Accountability of Government Agencies, Compliance with Laws and Regulations has a significant positive effect on the Performance Accountability of Government Agencies.